THE EFFECTIVENESS OF USING WHOLE BRAIN TEACHING METHOD IN THE TEACHING OF SPEAKING - Farikha, Ninik (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
Finding out how students communicate both before and after receiving instruction utilizing the whole brain teaching method is the aim of this study. The effectiveness of the whole brain teaching method in the Sibling English Course, as well as the notable difference in students' speaking abilities before and after instruction are both demonstrated. Because the outcome of this study is correlated with a numerical value that is derived quantitatively, a quantitative experimental design was adopted. Students in the foundational class of the Sibling English Course are the focus of this study. There are 20 pupils enrolled. Pre-test, treatment, and post-test were the three phases in the research process. (1) The research's findings indicate that students' speaking before receiving instruction utilizing the whole brain teaching approach falls between the "Fair" and "Good" categories, with an extent score ranging from 40–60 to 61–80. Value 68 is the greatest score, while 40 is the lowest. After using the whole brain teaching method, the students' speech falls into the "Good" to "Very Good" category, with an extent score ranging from 61-80 to 81-100. The minimum score is 76, and the maximum score is 92. (3) After adopting the whole brain teaching method, there is a noticeable difference in the speaking abilities of the students. The standard deviation is 5.394 in the post-test and 7.396 in the pre-test. Common Error The post-test mean is 1.206 and the pre-test mean is 1.654. (4) Students' speech improves when the whole brain teaching approach is used.